Seed characteristic variations and genetic structure of wild Zizania latifolia along a latitudinal gradient in China: implications for neo-domestication as a grain crop. Issue 6 (2nd December 2018) - Zhao, Yao; Zhong, Lan; Zhou, Kai; Song, Zhiping; Chen, Jiakuan; Rong, Jun
Abstract: Crop wild relatives are not only important genetic resources for crop improvement, but also domestication candidates for selecting new crops. As a close relative of American wild rice Zizania palustris, Z. latifolia is a perennial aquatic grass widely distributed in China. Although Z. latifolia has been domesticated and cultivated as an aquatic vegetable for >1000 years, a neo-domestication for grain production needs to be soundly evaluated. In this study, we investigated the seed characteristic variations and genetic structure of 15 Z. latifolia wild populations along a latitudinal gradient in China. Our results showed that Z. latifolia tended to produce relatively larger seeds with lower moisture content and lower investments in seed pericarp at lower latitudes. The width, size, shape, seed-pericarp ratio and relative water content of seeds were significantly associated with climatic variables. The seeds of Z. latifolia showed a relatively low germination percentage and strong dormancy, which might hinder the neo-domestication. In addition, high genetic differentiation had been found among Z. latifolia populations, which could be attributed to isolation by distance. This study offered preliminary information for the utilization and conservation of wild Z. latifolia . It suggested that the wild populations in the middle and lower reaches of the Yangtze River could be good candidates for grain crop domestication due to appropriate seed traits and high genetic diversity. The neo-domestication of wild Z. latifolia requires further researches on the genetic mechanism of the Domestication Syndrome and more works on artificial breeding. Abstract : Zizania latifolia is a perennial aquatic grass that has been domesticated as a vegetable in China. As a close relative of American wild rice Z. palustris, this species holds great potential in grain production. We found that Z. latifolia tended to produce larger seeds with lower moisture content and less investments in seed pericarp at lower latitudes. This suggested that the populations in the middle and lower reaches of the Yangtze River could be good candidates for grain crop domestication due to appropriate seed traits and high genetic diversity.